Performance Analysis of Multiuser Diversity in MIMO System With Antenna Selection Using MRC And SC - Khetrapal, Swati (My University, 2008)
Wireless communication is the way of transferring information from source to destination using the air as a medium i.e. without any wire or electric conductors. The next generation wireless systems are being designed to provide best broadband link access to information infrastructure. The recent technique for the telecommunication purpose uses the property of wireless communication like high speed wireless internet requires higher data rates and sufficiently good Quality of Service (QoS). However, transmission reliability is highly hampered by harsh propagation channels. To improve the transmission reliability Multiple Input Multiple Output (MIMO) system is used as it plays a vital role in supporting such high speed connections over radio cannels. In MIMO multiple copies of transmitted data is transmitted and is received at the receiver side using antenna diversity, and by doing so effect of fading is highly combat results in performance improvement of the system such as improvement in capacity of the system. Due to high hardware cost required for MIMO system, antenna selection system has been applied to MIMO system design which results in reduction in both cost and the complexity of the communication system. Along with antenna selection, combining techniques are also utilized for performance improvement of the communication system. Main selection combining are Maximal-Ratio Combining (MRC), Selection Combining (SC), and Equal-Gain Combining (EQC). In this thesis main focused is on MRC and SC combining and on the later part, comparison between both is made for better performance criteria. In the present work inherent property of Multi User Diversity (MUD) is used where Point-to-Multipoint (PMP) communication channel is taken. Thus, an overall system throughput is maximized by allocating channels to the user who can achieved largest throughput i.e. Signal to Noise Ratio (SNR) on it. This kind of diversity can be viewed as pouring more resources to the user with better channel quality. In this work an attempt has been made to analyze the performance of MUD in point-to-multipoint MIMO system with antenna selection with MRC and SC combining i.e. TAS/MRC and TAS/SC systems. In the TAS/MRC scheme, one of multiple transmits antennas, which maximizes the total received signal-to-noise ratio (SNR), is selected for uncoded data transmission based on the Channel State Information (CSI) feedbacks. Then the closed form expressions are derived for performance matrices i.e. outage probability, outage capacity and Symbol Error Rate (SER) of TAS/MRC and TAS/SC systems in Rayleigh fading. For the derivation of expressions, moment generating function based approach is used. By these expressions, it can be show that how and with what characteristics, antenna selection gains and MIMO configuration impacts the performance of the system. Both from theoretical and simulation results show that the outage probability and outage capacity of the TAS/MRC system is better than that of TAS/SC system. It is also seen that in multiuser PMP TAS/MRC and TAS/SC systems users can be viewed as a virtual transmitting antennas as number of user increases, performance of the system also increases in the same way as if number of transmitting antenna is increased. For SER, the main four modulation techniques are used (BPSK, QPSK, 8-PSK and 8-QAM). Simulation results show that out of these four modulation techniques BPSK has least SER and 8-QAM has better SER performance as compared to the 8-PSK modulation technique. After comparing different modulation techniques for TAS/MRC and TAS/SC system, it is concluded that the SER performance is better for TAS/MRC system than TAS/SC system for each digital modulation techniques.
M.E. (ECED)
Keywords: Wireless Communication